Governance by Things' as a challenge to regulation by law - Wolfgang Schulz; Kevin Dankert (Internet Policy Review, 2016)
In this paper the authors examine how the rise of the Internet of Things will challenge regulatory structures. Coming from the idea of "code as law" the shift from technology governing online spaces to physical spaces is described as a new phenomenon. They call it 'Governance by Things'. Some key observations of this structural shift are characterised in this article, for instance regarding its self-executing character and the imperfection of technology. Finally, the authors draw the conclusion that the 'Governance by Things' calls for a second-order regulation.
Keywords: 300; Governance by Things; Internet of things; Regulation; Private ordering